To Visit of the Visit A Critique of the Book: Exhibiting Photography - Mohammad Khodadadi Motarjemzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this paper, the author attempts to identify various aspects of values ​​and the shortcomings of the book by purposefully reviewing the book of "Exhibiting Photography" based on the four axes of the overall introduction  of the book and the author, external analysis and the origin of the book and its author, internal analysis and place of the book, and critique and evaluation of the book, and providing a good overview of its functional features and form. In this vein, the author, by drawing on a holistic view of the translations of photographic texts in Iran, outlines the general situation of the Iranian photography community at the time the book was published. Then, he analyzes the contents of the book in detail from the proposed perspective and evaluates the useful items and shortcomings of the book and concludes that despite the existing shortcomings, both in the structure of the book and in translation, the benefits of this book for the current photography community, and in particular the academic community, is far more than its shortcomings, provided it is favorably introduced to academic and art centers.